The barriers associated with emergency medical service use for acute coronary syndrome: the awareness and influence of an Australian public mass media campaign. - Cartledge, S.; Finn, Judith; Straney, L.; Ngu, P.; Stub, D.; Patsamanis, H.; Shaw, J.; Bray, Janet (2017)
BACKGROUND: Emergency medical services (EMS) transport to hospital is recommended in acute coronary syndrome (ACS) guidelines, but only half of patients with ACS currently use EMS. The recent Australian Warning Signs campaign conducted by the Heart Foundation addressed some of the known barriers against using EMS. Our aim was to examine the influence of awareness of the campaign on these barriers in patients with ACS. METHODS: Interviews were conducted with patients admitted to an Australian tertiary hospital between July 2013 and April 2014 with a diagnosis of ACS. Patient selection criteria included: aged 35-75 years, competent to provide consent, English speaking, not in residential care and medically stable. Multivariable logistic regression was used to examine factors associated with EMS use. RESULTS: Only 54% of the 199 patients with ACS interviewed used EMS for transport to hospital. Overall 64% of patients recalled seeing the campaign advertising, but this was not associated with increased EMS use (52.0%vs56.9%, p=0.49) or in the barriers against using EMS. A large proportion of patients (43%) using other transport thought it would be faster. Factors associated with EMS use for ACS were: age >65 years, ST-elevation myocardial infarction, a sudden onset of pain and experiencing vomiting. CONCLUSION: In medically stable patients with ACS, awareness of the Australian Warning Signs campaign was not associated with increased use of EMS or a change in the barriers for EMS use. Future education strategies could emphasise the clinical role that EMS provide in ACS.